2013
DOI: 10.1111/clr.12269
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implant–abutment connection, positioning of the machined collar/microgap, and platform switching on crestal bone level changes. Camlog Foundation Consensus Report.

Abstract: ObjectivesThe aim of this consensus meeting was to assess the impact of implant–abutment connection, positioning of the machined collar/microgap, and platform switching on crestal bone level changes.Materials and methodsTwo comprehensive systematic reviews were prepared in advance of the meeting. Consensus statements, practical recommendations, and implications for future research were based on within group as well as plenary scrutinization and discussions of these systematic reviews.ResultsPlacing the smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 2 publications
3
53
2
2
Order By: Relevance
“…Unlike the reports in the literature, the evidence from our study suggests that wearing a small platform diameter was a predictive factor for marginal bone loss. The difference in diameter size between our study and the previous ones might be a reasonable explanation for our divergent findings . Another possible explanation is that in our study the abutments presented equal diameters, regardless of the diameter of the implants.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Unlike the reports in the literature, the evidence from our study suggests that wearing a small platform diameter was a predictive factor for marginal bone loss. The difference in diameter size between our study and the previous ones might be a reasonable explanation for our divergent findings . Another possible explanation is that in our study the abutments presented equal diameters, regardless of the diameter of the implants.…”
Section: Discussioncontrasting
confidence: 97%
“…The tendency based on our results favors the platform switching technique to prevent or minimize implant marginal bone loss, compared with implants with platform matching abutments. It seems to be an issue only in situations in which a small volume of soft‐tissue thickness is observed around the implant . In addition, implant length above 8.5 mm was associated with increased marginal bone loss, as the increased contact area between the cortical bone and the implant interface results in higher cortical fixation.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, in the esthetic zone, it may be prudent to place the implant shoulder 0.5 to 1.0 mm subcrestal 47 so that a proper emergence profile can be achieved. Recent literature also found that subcrestal placement of the microgap 49,50 and the presence of a platform switch 51,52 aid in the preservation of the marginal bone level and, therefore, can be a useful feature in the anterior region where the implant can be placed slightly subcrestal. If the implant is placed too shallow, esthetic complications, such as poor contours of the restoration and visible metal margins, may ensue.…”
Section: Implant Positionmentioning
confidence: 99%
“…Effects of platform switching in limiting the peri-implant MBL have been discussed in both prospective and longitudinal human studies (3,9) and displayed long-term stability (15,16). Conversely, numerous studies have also reported results rejecting the platform-switching concept.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that both implants with matched and switched platform presented progressive bone loss. However, comparisons between different time intervals may be crucial to accurately confirm the concept of platformswitching (15). From the time point of prosthesis installation, which created a horizontal inward mismatch for the test group, to 1 year follow-up (T2-T1), a significant hMBL and BLa reduction occurred around switched platform implants and the linear regression showed a trend of higher MBL around matched platform implants over time.…”
Section: Discussionmentioning
confidence: 99%